Proyecto de implementación de una planta procesadora de palma africana para la producción de biodiésel como una alternativa de energía renovable para el parque automotor de la ciudad de quito - Tapia, Miriam (2009)
Even though the oil and natural gas accumulate under the earth superficies by process that last millions of years, the reserve seems to be ending with their use by mankind for less than a century. The atmosphere heating is the principal environment risk that mankind is facing to this day. Non population is out of the equation and its consequences. The two gases responsible of the phenom know as the “Greenhouse effect” is the CO2 and the methanol. In case of the dioxide of carbon, this occurs because of the high use of fossil oils (carbon and petroleum) as source of energy. The idea will be to use alternative fuels that are capable of reduce the concentration of dioxide of carbon in the atmosphere. One of the alternatives to solute this problem is the Biodiesel. When the actual oils (NAFTA, gas oil, fuel oil) are substitute (in a total or partial way), by this one, it can be achieve a balance more favorable of the gases that made the “Green house effect”. In Latin America, the transport is responsible of the 21% of the gases that cause the “Green House effect”. The transport sector will represent in Ecuador the 37.5% of the final consume of energy during the year 2007; in the city of Quito it will represent the 51.4% of the final consume of energy and the estimates for the year 2012 (efficient scenario) are of 47.64%, according to a study made by the Minister of Energy and Environment, published in the Dairy “Expreso” in the month of February 2007. The environment effects in the capital of Ecuador are, in the case, of first-importance, since the buses and trucks that uses diesel are responsible for 40% of the air-contamination in Quito, since studies made by Corpaire. The biodiésel is a direct and immediately substitute for the liquid oils use in transport and can be easily be integrated into the logistic systems that are actually operated in the city of Quito